ANALISIS IN-SILICO PROTEIN TIOL-DISULFIDA ISOMERASE FAMILI Bacillus - Kumaunang, Maureen (CHEMISTRY PROGRESS, 2010)
ABSTRACTKumaunang et al., 2010. Characterization of transcript genome product from Chaperone Bacillus sp. RP1.Protein folding is facilitated by chaperone molecule an folding catalyst.The aim of this research was to characterize the gene product of thiol-disulfide oxidoreductase gene from thermophylic organism Bacillus sp. Method used in this research were isolation and purification of deducted gene and characterization of gene product. The result showed that isolated gene has 1.4 kbp in length. Characterization of gene product indicated three proteins, Bdbdred, Bdbdox, and Etda, that have thioredoxin and DsbA motifs, and also active site and bonding site with Zn. Structure prediction of these three proteins showed similarity among them.Keywords : chaperone, thiol-disulfide oxidoreductase, thioredoxin, DsbA, Bdbd